Energetic Analysis in a Spray Drying Process - Alex Notaroberto Madeira; Carlos Alberto Chaves; Wendell de Queiróz Lamas (Journal of Advanced Thermal Science Research, 2020)
The present work aims in evaluate the installation of an equipment of spray drying, by psychrometry technique, analyse the power sources consumption and relates with the productivity of the equipment, by energy auditory. This work consists in comparing the evaporation capacity of a 750 kg/h of water spray dryer and the amount of water that comes from atmospheric air, where the equipment consumes 160 kWh and 80 kg of LGP/h. Therefore, this work demonstrates that to project a spray dryer it must be analysed these water mass values in atmospheric air and be contemplated a dehumidifier in order to prevent so significant and different losses in different periods of the same day.